Being Bold: How HFES Can Encourage Responsible, Timely and Participative Ergonomics to Address Societal Issues. (September 2021) - Wooldridge, Abigail R.; Rogers, Courtney C.; Reid, Christopher R.; Valdez, Rupa S.; Endsley, Mica; Holden, Richard J.; Sommerich, Carolyn M.; Thatcher, Andrew
Human Factors/Ergonomics (HF/E) is a systems discipline focused on jointly optimizing human well-being and overall system performance. Societal problems, including but not limited to health inequity, racism, poverty, and (lack of) sustainability, are inherently systems problems that involve humans, and so recent work has argued that HF IE can and should contribute to addressing these issues. This panel will bring together leaders of the Human Factors and Ergonomics Society (HFES) to discuss if and how HFES can encourage and support responsible, timely, and participative ergonomics to address societal issues. The session will be highly interactive as the organizers will moderate discussion to reflect on the progress the science and Society (i.e., HFES) have made in this space, identify areas for improvement, and creatively consider future actions to ensure our science and Society are responding to these issues in an ethical manner.